Material paradidático: uma proposta investigativa para o ensino de química orgânica no ensino médio - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
The main objective of this study is to develop a paradidactic material containing experimental scripts in the Teaching of Organic Chemistry, for Chemistry teachers, to facilitate student learning in the contents of high school chemistry and help teachers and professionals in the area to insert experimental practices in everyday school life, favoring the construction of scientific knowledge and effective learning through investigative experimentation. For the material elaboration, an analysis of the 3rd grade high school chemistry textbooks was initially performed according to some criteria, so that the material could be elaborated in the best way to be applied in the classroom, using alternative materials found in the Amapaense culture, which can be applied inside or outside a Chemistry Laboratory. After the analysis of the textbooks, it was found that none of them satisfy all the criteria, thus, the paradidactic material aims to contribute in an attempt to remedy some difficulties of insertion of experimental classes in elementary schools, allowing students and teachers to have access to the material, contributing to the improvement of teaching-learning, facilitating the understanding of the contents of chemistry more effectively, making this knowledge become important in life for students
Keywords: Química (Ensino médio) - Estudo e ensino; Química - Experiências; Ensino-aprendizagem; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA